2016
DOI: 10.3390/met6080189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Creep Aging Process on Microstructures and Properties of the Retrogressed Al-Zn-Mg-Cu Alloy

Abstract: Abstract:The creep aging behaviors of retrogressed Al-Zn-Mg-Cu alloy were studied by uniaxial tensile creep tests at 140 • C. The effects of creep aging time and applied stress on microstructures and properties of the studied alloy were investigated by using transmission electron microscope (TEM), hardness, and corrosion resistance tests. Results show that the effects of the creep aging process on microstructures and properties are significant. The size of matrix precipitate (MPt), distance between MPts, width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Figure 2 shows the EBSD phase identify results of the as-spray-deposited alloy. MgZn 2 Figure 1 shows back-scattered electros images (BSE) and XRD of the as-spray-deposited Al-ZnMg-Cu-Zr alloy. The average grain size was about 50 ± 10 μm after measurements (more than 60 grains were counted and measured from BSE SEM images).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows the EBSD phase identify results of the as-spray-deposited alloy. MgZn 2 Figure 1 shows back-scattered electros images (BSE) and XRD of the as-spray-deposited Al-ZnMg-Cu-Zr alloy. The average grain size was about 50 ± 10 μm after measurements (more than 60 grains were counted and measured from BSE SEM images).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4]. Their excellent performance attracts much interest from the manufacturing industry [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various methods have been developed to enhance corrosion resistances of Al alloys, such as corrosion inhibitor [5], mechanical alloying [6], aging process [7,8], laser treatment [9] and friction stir welding [10]. In addition, Kaseemet al have reported an oxide film on 7075 Al alloy with enhanced corrosion resistance in 3.5% NaCl solution via the micro-arc oxidation process [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, 7xxx series alloys are being used in the aerospace and high-speed train system for structural components due to their high strength/weight ratio [7][8][9][10][11][12]. 7xxx series alloys are mainly applied in the form of rolled plates or extruded sections, and the static or dynamic recrystallization is easy to occur during hot working and heat treatment.…”
Section: Introductionmentioning
confidence: 99%